Overview of Menstrual Patterns in Female Patients Diagnosed with Tuberculosis with a History of Infertility at DOTS Polyclinic Hasan Sadikin Hospital and Community Health Centers in Bandung City - Madjid, Tita Husnitawati; Utomo, Suhendro Rahmat; Susilo, Artha Falentin Putri; Ritonga, Mulyanusa Amarullah; Arya, Insi Farisa Desy (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Female genital tuberculosis (FGTB) is one of the leading causes of infertility in countries with high cases of tuberculosis. However, there is a lack of data showing the menstrual patterns of FGTB patients in Indonesia. This study was conducted to describe the menstrual patterns of female patients diagnosed with TB and who have a history of infertility at the Directly Observed Treatment Short Course Polyclinic of Hasan Sadikin Hospital and community health centers in Bandung City.Method: This is a descriptive observational study using primary data. The subjects were outpatient TB patients with a history of infertility in the Directly Observed Treatment Short Course polyclinic of Hasan Sadikin Hospital and community health centers in Bandung City from 2018 to 2022. Data collection was conducted through questionnaire-based interviews.Results: Out of 950 TB patients of childbearing age recorded in medical records, 41 patients matched the specified criteria. The menstrual disorders experienced by patients included polymenorrhagia, oligomenorrhea, amenorrhea, prolonged menstrual cycles, irregular cycles, hypomenorrhea, heavy menstrual bleeding, and intermenstrual bleeding.Conclusion: The most common menstrual disorders in TB patients with a history of infertility were irregular cycles (36.6%), hypomenorrhea (31.7%), and oligomenorrhea (19.5%).Gambaran Pola Menstruasi pada Pasien Perempuan dengan Diagnosis Tuberkulosis dan Riwayat Infertilitas di Poli DOTS RSHS dan Puskesmas Kota BandungAbstrakPendahuluan: Female genital tuberculosis merupakan salah satu penyebab utama infertilitas pada negara dengan kasus tuberkulosis yang tinggi. Sebagai salah satu dari gejalanya, belum ada data yang menunjukkan pola menstruasi dari pasien female genital tuberculosis di Indonesia. Penelitian ini bertujuan untuk mengetahui gambaran pola menstruasi pada pasien wanita dengan diagnosis tubekulosis dan memiliki riwayat infertilitas di Poliklinik Directly Observed Treatment Short Course Rumah Sakit Hasan Sadikin dan Puskesmas Kota Bandung.Metode: Penelitian deskriptif dengan menggunakan data primer. Subjek penelitian adalah pasien tuberkulosis wanita dengan riwayat infertilitas yang dirawat jalan di poliklinik Directly Observed Treatment Short Course Rumah Sakit Hasan Sadikin dan 4 Puskesmas di Kota Bandung dari tahun 2018 - 2022. Subjek diperoleh melalui wawancara berbasis kuesioner.Hasil: Dari 950 pasien tuberkulosis wanita usia subur yang terdata di rekam medis, didapatkan 41 data pasien yang sesuai dengan kriteria yang ditentukan. Gangguan menstruasi yang dialami pasien dapat berupa polimenore, oligomenore, amenore, siklus menstruasi yang memanjang, siklus yang irreguler, hipomenore, heavy menstrual bleeding, dan perdarahan intermenstrual.Kesimpulan: Gangguan menstruasi yang paling sering terjadi pada pasien TB dengan riwayat infertilitas adalah siklus yang irreguler (36.6%), hipomenore (31.7%), dan oligomenore (19.5%).Kata Kunci: Infertilitas, Kota Bandung, Pasien TB wanita, Pola Menstruasi.